2022
DOI: 10.3390/waste1010002
|View full text |Cite
|
Sign up to set email alerts
|

Spent Coffee Grounds Characterization and Reuse in Composting and Soil Amendment

Abstract: As an everyday beverage, coffee is consumed worldwide, generating a high amount of waste after brewing, which needs attention for its disposal. These residues are referred to as spent coffee grounds (SCGs), which have been shown to have applications as polymers/composites precursors, biofuels, and biofertilizers. This review focuses on agricultural applications usually based on organic matter to fertilize the soil and consequently improve plant growth. To date, SCGs have been shown to exhibit outstanding perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 124 publications
(208 reference statements)
0
15
0
Order By: Relevance
“…It is worth highlighting that cf contain ca. 1.8-2.8% nitrogen [16,19] from, e.g. proteins and caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth highlighting that cf contain ca. 1.8-2.8% nitrogen [16,19] from, e.g. proteins and caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation products during roasting include the carcinogen, acrylamide; practical solutions to reduce acrylamide production were proposed [ 33 ]. The SCG remaining after production of hot-brew coffee include carbohydrates such as 8–15% celluloses and 30–40% hemicelluloses, 20–30% lignins, 7–21% lipids and minerals, and 13–17% proteins, together with phenolic compounds (12 mg/g), caffeine (14.5 µg/g) and CGA (31.8 µg/g) [ 34 ]. Further, isolation and characterisation of these components were reviewed [ 34 ].…”
Section: Bioactive Ingredients Of Scgmentioning
confidence: 99%
“…The SCG remaining after production of hot-brew coffee include carbohydrates such as 8–15% celluloses and 30–40% hemicelluloses, 20–30% lignins, 7–21% lipids and minerals, and 13–17% proteins, together with phenolic compounds (12 mg/g), caffeine (14.5 µg/g) and CGA (31.8 µg/g) [ 34 ]. Further, isolation and characterisation of these components were reviewed [ 34 ]. Similar information on SCG produced after cold-brew extraction processes is not available.…”
Section: Bioactive Ingredients Of Scgmentioning
confidence: 99%
“…The analysis revealed that all eggshells exhibited consistent chemical composition, primarily composed of CaCO3, along with trace amounts of other elements such as S, Mg, P, Al, K, and S. [15] Minerals constitute a portion of the chemical composition of coffee grounds, where the most prevalent minerals extracted from coffee grounds include potassium, phosphorus, magnesium, and calcium. [16][17][18][19] The diverse array of nutrient-rich compounds extracted from coffee grounds [20] banana peels and egg shells can potentially offer a multitude of applications, particularly in the field of agriculture as fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Minerals constitute a portion of the chemical composition of coffee grounds, where the most prevalent minerals extracted from coffee grounds include potassium, phosphorus, magnesium, and calcium. [ 16–19 ] The diverse array of nutrient‐rich compounds extracted from coffee grounds [ 20 ] banana peels and egg shells can potentially offer a multitude of applications, particularly in the field of agriculture as fertilizers.…”
Section: Introductionmentioning
confidence: 99%